Quality of Work Life (QWL) pada Karyawan Pelaksana Afdeling PT Perkebunan Nusantara IV Regional III, Kebun Sei Garo - Paune Boni Tua Butar-Butar; Siti Aisyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the level of Quality of Work Life (QWL) among operational employees at PT. Perkebunan Nusantara IV Regional III, Kebun Sei Garo. The research sample consists of 90 operational employees from PT. Perkebunan Nusantara IV Regional III, Kebun Sei Giro, using a total sampling technique. The data collection method employed is a descriptive quantitative approach utilizing a QWL scale based on a four-point Likert scale. The research instrument comprises 84 items. The findings show that the average QWL score is 268.95 with a standard deviation of 41.85, and the data are normally distributed (Kolmogorov-Smirnov sig = 0.090). Generally, Afdeling II and IV exhibit the highest levels of QWL, particularly in aspects of compensation, working conditions, and job opportunities. In contrast, Afdeling III demonstrates a lower level of QWL, especially concerning social relevance and job opportunities. In conclusion, the QWL of operational employees at PT. Perkebunan Nusantara IV Regional III, Kebun Sei Garo is at a high level; however, special attention and targeted interventions are needed for Afdeling III to enhance work quality and employee motivation.